Excitotoxicity Alters Endogenous Secretoneurin Plasma Levels, but Supplementation with Secretoneurin Does Not Protect Against Excitotoxic Neonatal Brain Injury. (1st July 2019) - Posod, Anna; Wechselberger, Karina; Schmid, Anna; Huber, Eva; Urbanek, Martina; Kiechl-Kohlendorfer, Ursula; Griesmaier, Elke
Abstract: Excitotoxicity plays an important role in the pathogenesis of developing brain injury. The neuropeptide secretoneurin (SN) has neuroprotective potential. The aim of this study was to investigate SN plasma concentrations following excitotoxicity and to evaluate the effect of SN as therapeutic strategy in excitotoxic newborn brain injury. Baseline SN plasma concentrations were established in healthy animals. To evaluate the effect of an excitotoxic insult on SN levels, mice pups were subjected to an intracranial injection of ibotenic acid and SN plasma concentrations were measured thereafter. To assess SN's neuroprotective potential, a subgroup of animals was randomly assigned to the following groups: i) "single treatment": vehicle 1 × phosphate-buffered saline (PBS), SN 0.25 μg/g body weight (bw), SN 2.5 μg/g bw or SN 12.5 μg/g bw in a single dose 1 h after insult; ii) "acute repetitive treatment": vehicle 1 × PBS or SN 0.25 μg/g bw every 24 h starting 1 h after insult; iii) "delayed repetitive treatment": vehicle 1 × PBS or SN 0.25 μg/g bw every 24 h starting 60 h after insult. Animals subjected to excitotoxic injury showed significantly lower SN plasma concentrations 6 and 120 h after insult in comparison to healthy controls. Administration of SN did not positively affect lesion size, apoptotic cell death, microglial cell activation or cell proliferation. To conclude, endogenous SN plasma levels are lower in newborn mice subjected to an excitotoxic insult than in healthy controls. Supplementation with SN in various treatment regimens is not neuroprotective in the experimental animal model of excitotoxic newborn brain injury. Highlights: Secretoneurin (SN) is a neuropeptide with neuroprotective potential. Experimental excitotoxic newborn brain injury alters endogenous SN plasma levels. Administration of SN does not protect against excitotoxic injury in newborn mice.